Comprehension of scientific metaphors: Complementary processes revealed by ERP. (May 2017) - Tang, Xuemei; Qi, Senqing; Jia, Xiaojuan; Wang, Botao; Ren, Wei
Abstract: In order to complement current debates and open questions in the field of figurative language comprehension, the current paper investigated how metaphors from different kinds of contexts are electrophysiologically processed. For the first time, we compared comprehension of scientific metaphors with that of conventional ones using event-related potentials (ERPs). Scientific metaphors have the unique semantic structure with two different contexts and inference involvement for knowledge-understanding. By time-locking the N400 and later LPC time windows, the present study shows the different stages of meaning integration when comprehending figurative language. The N400 amplitudes to the last word of the sentence varied as a function of expression type in a graded manner increasing from literal sentences to conventional metaphors, and to scientific metaphors. N400s elicited by scientific metaphors showed central-parietal-right-biased scalp distributions. Scientific metaphors also elicited a late negativity in the LPC window simultaneously on the left and right hemispheres suggesting further attempts to integrate meaning when scientific inference is involved. These findings of scientific metaphors might test some related metaphor-processing models to a greater extent. The reported results also demonstrate that the left and right hemispheres of the brain work together in a complex dynamic pattern during literal and figurative language comprehension and that the right hemisphere is necessarily involved, but not sufficient, for understanding metaphoric expressions. Highlights: We used scientific metaphors as the novel ones in the ERP experiment. The more complicated contextual structure of scientific metaphors enhances the difficulty of meaning integration. The inference of scientific metaphors further enhances the cognitive taxing for a secondary integration of meaning. The right hemisphere might have its special role in scientific metaphor processing.